2009
DOI: 10.5172/ijpl.5.1.49
|View full text |Cite
|
Sign up to set email alerts
|

EFL proficiency level and differences in Japanese secondary school students’ views on the need for pedagogical change

Abstract: This research focuses on Japanese high school students' views about EFL pedagogy and investigates whether their views differ according to their English language proficiency level as measured by the STEP test and their teachers' pedagogical approach. It explores in greater depth this aspect of a larger study conducted by Ingram, Kono, O'Neill and Sasaki (2008). The views of those who performed at a higher level on the STEP test were compared with the views of those who reported lower levels of performance on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…This issue implies that further research is required to assess Iranian students' computer literacy levels and identify the necessary computer and Internet skills for the effective implementation of online instruction. This finding is commensurate with the results of studies which have shown that EFL students had low levels of computer literacy in the other EFL contexts (Bataineh and Baniabdelrahman 2006;Lockley 2011;Murray and Blyth 2011;O'Neill 2009).…”
Section: Discussionsupporting
confidence: 89%
“…This issue implies that further research is required to assess Iranian students' computer literacy levels and identify the necessary computer and Internet skills for the effective implementation of online instruction. This finding is commensurate with the results of studies which have shown that EFL students had low levels of computer literacy in the other EFL contexts (Bataineh and Baniabdelrahman 2006;Lockley 2011;Murray and Blyth 2011;O'Neill 2009).…”
Section: Discussionsupporting
confidence: 89%